Psychology for lawyers : understanding the human factors in negotiation, litigation, and decision making - Robbennolt, Jennifer K.; Sternlight, Jean R.; American Bar Association. Section of Dispute Resolution (Chicago, Illinois : American Bar Association, Dispute Resolution Section, 2021)
'The primary goal of this book is to expose lawyers and law students to some of the key insights offered by the field of psychology and to illustrate the ways in which understanding these insights can improve the practice of law'--
Perceiving and understanding the world -- Memory -- Emotion -- Judgment shortcuts -- Decision making -- Persuasion and social influence -- Interpersonal communication -- Justice -- Interviewing clients and witnesses -- Counseling clients -- Negotiating and mediating -- Discovery and due diligence -- Writing -- Ethics -- On being productive, successful, and happy.
Puan Shaizimah Badzri/ Ketua Perpustakaan Undang-Undang/ shai@ukm.edu.my/ 0389216939/ OC/ Areesh Education & Trading
Includes bibliographical references and index.
Keywords: Law -- Psychological aspects; Practice of law -- United States; Lawyers -- United States; Trial practice -- United States